Genetic Analysis of ABO and RH Blood Groups in Scheduled Caste Populations of Patna District (Bihar), India: Investigating ABO and RH blood groups in scheduled caste populations of Patna District, Bihar, India (Journal of Advances and Scholarly Researches in Allied Education, 2019)
A series of glycoprotein and glycolipids on red blood cell surface constitute blood group antigens. These are A, B, AB and O in ABO blood group system and Rh in rhesus blood group system. These antigens are genetically controlled. Certain diseases have been shown to be associated with certain blood groups. In present study an attempt is made to study the distribution of ABO and Rh. (D) blood group systems among the Scheduled caste population of District of Patna, Bihar, India. The study was restricted to four Prominent Scheduled Caste, namely the Dusadhs, the Chamars, the Pasis the Musahars, residing in an around Patna, Bihar. The data were collected from the random sample of the persons who were subjected to immuno-haematological test to ascertain the prevalence of four different blood groups (A, B, AB O) in them.All the populations exhibited different patterns of the incidence of ABO blood groups in them. Bloodgroup A was most prevalent (37.22) among the Pasis in both the sexes. Blood group Bwas most frequent (34.11) in both the sexes of Dusadhs. Among the Chamars, the blood group with highest incidence was AB (27.14 ).Bloodgroup O was most abundant among the Musahars (37.20). The frequency of IO allele was found over 60 among the Musahars,but less than50 among the remaining three populations. The frequency of IB¬ alleale was approximately 30 among the Dusadhs and the Chamars, but decreased down to around 20 among the Pasis and the Musahars. The frequency of IA allele was higher among the Pasis (30), but varied from 17 to 23 among the remaining three populations. The Musahars, therefore, appeared to have a distinct pattern of ABO blood groups and the frequencies of blood group alleles, compared to the remaining three Scheduled castes.